2019
DOI: 10.1093/biolre/ioz217
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid steroid profile in sows: relationship to follicle size and oocyte quality†

Abstract: Identification of reliable characteristics of follicle quality and developmental competence has been pursued in numerous studies, but with inconsistent outcomes. Here, we aimed to identify these characteristics by analysis of the follicular fluid (FF) steroid profile in relation to cumulus-oocyte complex (COC) morphology and follicle size, followed by molecular substantiation. Multiparous sows at weaning were used to facilitate analysis at the start of the follicular phase of the oestrus cycle. Sows with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Moreover, estradiol and progesterone can improve porcine and bovine oocyte developmental competence during in vitro maturation, when supplemented at the optimal time and dosage [ 8 ]. Costermans et al reported that β-estradiol levels are positively associated with follicle size and not surprisingly sows with a high percentage of healthy COCs have higher follicular fluid levels of β-estradiol and progesterone [ 9 ]. Although studies have emphasized the association between steroid hormone profiles and follicle development, the molecular mechanisms underlying the way steroidogenesis affects follicular atresia are less well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, estradiol and progesterone can improve porcine and bovine oocyte developmental competence during in vitro maturation, when supplemented at the optimal time and dosage [ 8 ]. Costermans et al reported that β-estradiol levels are positively associated with follicle size and not surprisingly sows with a high percentage of healthy COCs have higher follicular fluid levels of β-estradiol and progesterone [ 9 ]. Although studies have emphasized the association between steroid hormone profiles and follicle development, the molecular mechanisms underlying the way steroidogenesis affects follicular atresia are less well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding and protein-coding RNAs have been widely studied in the reproductive system, including in ovary, oocyte, and granulosa cells [ 32 , 33 , 34 ]. However, studies on chicken follicle development based on changes in LH concentration to explore the functional coregulation of lncRNAs and mRNAs are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes that originate from small (<3 mm) follicles are less likely to mature to metaphase II (MII) or develop to the blastocyst stage compared to oocytes derived from medium (3-5 mm) and large (>5 mm) follicles [21]. Moreover, larger follicles (>5 mm) have been shown to have higher β-estradiol concentrations, and high quality COCs from these follicles have increased abundance of transcripts involved in ovarian steroidogenesis [22]. Historically, cumulus cell expansion has been considered to be required for successful maturation in vitro and often the degree of cumulus cell expansion is correlated with improved oocyte maturation [23,24].…”
Section: Selection Criteriamentioning
confidence: 99%
“…Historically, cumulus cell expansion has been considered to be required for successful maturation in vitro and often the degree of cumulus cell expansion is correlated with improved oocyte maturation [23,24]. As another factor to consider, oocyte quality is also impacted by the energy status of the female as feed restriction (50% per day) during the last two weeks of lactation decreased follicle size, concentration of steroids in the follicular fluid, and maturation to MII [22].…”
Section: Selection Criteriamentioning
confidence: 99%